2020
DOI: 10.1186/s12889-020-09585-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of physicians during COVID-19 pandemic: a cross-sectional study in Lebanon

Abstract: Background As the Coronavirus disease 2019 (COVID-19) pandemic continues to evolve, physicians must be equipped with adequate knowledge, skills on the prevention measures, and confidence in diagnosing and treating COVID-19 patients. Therefore, it is of great interest to assess the knowledge and practices of Physicians to identify existing gaps and improve occupational safety and viral surveillance. Methods A cross-sectional study was conducted in Lebanon between 28th March and 11th April 2020. Data was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
7
29
2
Order By: Relevance
“…The present study also revealed that more than 74.6% of the surveyed OBGYNs were afraid of getting infected with COVID-19 due to their occupational exposure, and approximately all of them were afraid of transmitting COVID-19 to their family member in the case they got infected. Our results are in line with the ndings of studies conducted in Lebanon, Egypt and, Denmark (27,31,32).…”
Section: Fearssupporting
confidence: 93%
See 2 more Smart Citations
“…The present study also revealed that more than 74.6% of the surveyed OBGYNs were afraid of getting infected with COVID-19 due to their occupational exposure, and approximately all of them were afraid of transmitting COVID-19 to their family member in the case they got infected. Our results are in line with the ndings of studies conducted in Lebanon, Egypt and, Denmark (27,31,32).…”
Section: Fearssupporting
confidence: 93%
“…The majority of OBGYNs (65.6%) had an overall good level of knowledge and only 1% of them had a poor level of knowledge (<60%). This result is in line with that of Abou Abass et al, who reported that 89.5% of Lebanese physicians have a good knowledge regarding COVID-19 (27). Future plans should focus on improving the knowledge of OBGYNs with moderate knowledge levels.…”
Section: Knowledgesupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, the authors reported that physicians with an experience of 10 years and above were 3.35 times more likely to have good practice than their counterparts. 35 In contrast, Saqlain et al reported in their study among HCWs in Pakistan that pharmacists had greater knowledge than doctors, but the difference was not significant. 36 In contrast, Bhagavaathula et al found that doctors had greater knowledge than pharmacists.…”
Section: Discussionmentioning
confidence: 84%
“…In Lebanon, there is a lack of data concerning the number of cleaning staff infected by COVID-19 among hospitals but according to the epidemiological surveillance unit data, no deaths were reported among this category. Although those previous studies have evaluated the knowledge and practices of different health care workers toward COVID-19 including physicians (9), dentists (10), pharmacists (11) and nurses (12) no studies have focused on the practices of hospital services staff members, particularly housekeepers.…”
Section: Introductionmentioning
confidence: 99%